About features of statistical algorithms for identifying stable word chains - Червяк, Александр Васильевич; Вечур, Александр Владимирович; Шевченко, Елена Леонидовна; Ляпота, Виталий Николаевич (Eastern-European Journal of Enterprise Technologies, 2011)
This article discusses a method to identify stable word chains, particularly his work in various versions and with different parameters. The proposed method can be implemented as part of a workstation for the linguist compiling dictionaries phrases